Resultados materno perinatales en gestantes con ruptura prematura de membranas de 28 a 34 semanas con el uso de Cefadroxilo posterior al término de la antibioticoterapia estándar - Carbonell Julca, Enrique Manuel (2019)
Introduction: The premature rupture of the membranes is a complication of pregnancy, which, in the case of establishing an adequate treatment with an increase in maternal and perinatal morbidity and mortality. Objective: To determine the adverse perinatal maternal outcomes with the use of cefadroxil after the end of standard antibiotic therapy with standard antibiotic therapy alone in pregnant women with premature membrane rupture from 28 to 34ss. Method: This study corresponds to a Cohort study, retrospective. In which the population is divided into two cohorts: cohort 1 (puerperals with rpm from 28 to 34ss with standard standard antibiotic therapy) and cohort 2 (puerperal women with 28-34ss rpm with cefadroxil after standard antibiotic therapy) and analyze the results of the search. Perinatals of each of them. Conclusion: There is a difference in the results of perinatal materials with the use of cefadroxil after standard antibiotic therapy than only standardized antibiotic therapy.